2015
DOI: 10.1002/chem.201500319
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Biphenylene‐Containing Diazaacenes

Abstract: We describe the efficient synthesis of substituted benzo[3,4]cyclobuta[1,2-b]phenazine, benzo[3,4]cyclobuta[1,2]benzo[1,2-i]phenazine, and benzo[3,4]cyclobuta[1,2-b]naphtho[2,3-i]phenazine by a condensation reaction of aromatic diamines with the stable biphenylene-2,3-dione.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 37 publications
5
36
0
Order By: Relevance
“…Cyclic voltammetry measurements show the influence of the structure on the first reduction potential (Table ). The elongation of the acene backbone for 16 results in destabilization of the LUMO owing to the formally anti‐aromatic cyclobutadiene unit in accord with our earlier findings . A higher frontier molecular orbital (FMO) gap results.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Cyclic voltammetry measurements show the influence of the structure on the first reduction potential (Table ). The elongation of the acene backbone for 16 results in destabilization of the LUMO owing to the formally anti‐aromatic cyclobutadiene unit in accord with our earlier findings . A higher frontier molecular orbital (FMO) gap results.…”
Section: Resultssupporting
confidence: 86%
“…Heating the reaction mixture produced a mixture of unknown compounds with only a small amount of 15 . The coupling of 13 to biphenylene dione gives 16 , featuring an extended π‐system with an anti‐aromatic unit attached to the azaacene core …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the development of powerful syntheticc oncepts to prepare soluble and processible derivatives of otherwise difficult to dissolve larger azaacenes,b ut also the discoveryo ft heir spectacular nchannel transport properties by Miao has boosted the visibility and utility of these materials. [8] We have already synthesized as eries of unsymmetrical biphenylene-substituted azaacenes, but the synthesis of symmetrical azaacenes is more challenginga nd desirable for their potential applicationi no rganic electronics. [6] While in Vollhardt's phenylenes,t here is as trict sequence of benzenea nd cyclobutadiene units,S wager extended the concept to larger acenes and successfully interspersed cyclobutadienee lements between anthracene units and demonstrated that thesem aterials are attractive emitters.…”
Section: Introductionmentioning
confidence: 99%
“…[6] While in Vollhardt's phenylenes,t here is as trict sequence of benzenea nd cyclobutadiene units,S wager extended the concept to larger acenes and successfully interspersed cyclobutadienee lements between anthracene units and demonstrated that thesem aterials are attractive emitters. [7][8][9][10] [a] Dr.P . [8] We have already synthesized as eries of unsymmetrical biphenylene-substituted azaacenes, but the synthesis of symmetrical azaacenes is more challenginga nd desirable for their potential applicationi no rganic electronics.…”
Section: Introductionmentioning
confidence: 99%